A Preliminary Study of Pre-Season Taekwondo Preparation Strategy: Personal Isolation Training Effect for Elite Athletes - Sung, Yu-Chi; Yang, Yi-Zhen; Chang, Che-Chia; Chou, Chun-Chung (International Journal of Environmental Research and Public Health, 2021)
Background: The global coronavirus disease pandemic (COVID-19) has had a considerable impact on athletic competition and team sports training. Athletes have been forced to train alone at home. However, the isolation training model effects are still unknown. Purpose: This study compared the effects of personal isolation training (PIT) and detraining (DT) on specific sport performances (flexibility, power, reaction time, acceleration, and aerobic capacity) and body composition in elite taekwondo athletes. Methods: Eleven elite taekwondo athletes were recruited as voluntary subjects. Athletes were randomly paired by weight into the personal isolation training group (PIT group: N = 5, age: 21.2 ± 0.4 years, BMI: 22.2 ± 0.8 kg/m2) or detraining group (DT group: N = 6, age: 19.8 ± 0.3 years, BMI: 23.1 ± 1.0 kg/m2). All subjects performed the same training content prior to the pre-test (T1). When the pre-test was completed, all subjects underwent 12 weeks of PIT or DT. Athletes were then administrated the post-test (T2). The athlete’s sport performances and body composition were measured to compare the differences between the two groups (PIT and DT) and two phases (T1 and T2). Results: There were no significant differences in kicking reaction time and flexibility in both groups (p > 0.05). The PIT showed significant improvements in 10 m (10M) sprint performance (p < 0.05), and displayed a progress trend in Abalakov jump performance. In addition, the PIT resulted in a better change response in 10M sprint performance (PIT: −4.2%, DT: +2.1%), aerobic endurance performance (PIT: −10.2%, DT: −18.4%), right arm muscle mass (PIT: +2.9%, DT: −3.8%), and trunk muscle mass (PIT: +2.2%, DT: −1.9%) than DT (p < 0.05). The fat mass percentage showed a negative change from T1 to T2 in both groups (p < 0.05). Conclusions: PIT showed a trend toward better body composition (arm and trunk muscle) and sport performances (10M sprint and aerobic capacity) compared to DT. This finding may provide information on the effectiveness of a personal isolation training model for optimal preparation for taekwondo athletes and coaches. It may also serve as a useful and safe guideline for training recommendations during the coronavirus disease (COVID-19).